Protection of Personal Data in The Implementation of Cyber Notary Based on Law Number 27 Of 2022 Concerning Protection of Personal Data in Conjunction with Law Number 19 of 2016 Concerning Amendments to Law Number 11 of 2008 Concerning Information and Electronic Transactions - Ratna Dewi, Iriani (Magister Kenotariatan Universitas Pasundan, 2024)
Developments in the notarial world are known as the Cyber Notary system; this opportunity also raises challenges regarding the vulnerability of data misuse in cyberspace. The purpose of this research is to see how personal data is used by Notaries in the implementation of a Cyber Notary, as well as the extent of the notary's responsibility for this Personal Data according to the Personal Data Protection Law in conjunction with the Electronic Transaction and Information Law. This research uses a normative juridical approach, emphasizing library research, to obtain secondary data. The research specifications used are analytical descriptive. The research stage was library research, which was then supported by field research. The data collection techniques that have been collected are analyzed qualitatively. The research results show that the Personal Data Protection Law provides legal certainty regarding the responsibility of the Notary as Data Controller in using the Personal Data of the Applicant, as well as providing limitations to the notary regarding the extent of responsibility for the security of the personal data belonging to the notary by the notary which is also regulated in Article 15, 16, 17 and 19 of the Information and Electronic Transactions Law that the notary must be reliable and guarantee the security and confidentiality of the client or party concerned. Regulations regarding personal data protection protect and guarantee citizens' fundamental rights, provide legal certainty to citizens and protect notaries in carrying out their duties.